An analysis of two-dimensional stratified gravity current flow using open FOAM - Lam W.K.; Chan L.; Hasini H.; Ooi A. (Science Publishing Corporation Inc, 2023)
Direct numerical simulations (DNSs) of two-dimensional stratified gravity-current are simulated using OpenFOAM. Three different aspect ratio, h 0 /l 0 (where h 0 is the height of the dense fluid and l 0 is the length of the dense fluid) are simulated with stratification ranging from 0 (homogenous ambient) to 0.2 with a constant Reynolds number (Re) of 4000. The stratification of the ambient air is determined by the density difference between the bottom and the top walls of the channel (? b - ? 0 , where ? b is the density at the bottom of the domain and ? 0 is the density at the top). The magnitude of the stratification (S=? b /?) can be determined by calculating the reduced density differences of the bottom fluid with the ambient fluid (? b = (? b - ? 0 )/ ? 0 ) and the dense fluid with the ambient fluid (? = (? c -? 0 )/ ? 0 , where ? c represents the density of the dense fluid). The configuration of the simulation is validated with a test case from Birman, Meiburg & Ungraish and the contour and front velocity (propagation speed) were in good agreement. The gravity current flow in the stratified ambient is analyzed qualitatively and compared with the gravity current in the homogenous ambient. Gravity current in homogenous ambient (S=0) and weak stratification (S=0.2) are supercritical flow where the flow is turbulent and Kelvin-Helmholtz (K-H) billow formed behind the gravity current head. The front location of the gravity is reduced as the stratification increase and denotes that the front velocity of the gravity current is reduced by the stratification. 2018 Authors.